PrEP uptake and persistence amongst HIV-negative women who exchange sex for money or commodities in Kampala, Uganda: A qualitative inquiry assessing the influence of pregnancy. - Shivali Joshi; Catherine Namuddu; Francis Xavier Kasujja; Miriam Mirembe; Jaco Homsy; Janet Seeley; Rachel King (Public Library of Science (PLoS), 2023)
Pregnant young women who exchange sex for money or commodities are at elevated biological and social risk for HIV acquisition. PrEP serves as an effective means of HIV prevention, including during pregnancy. This study aimed to explore attitudes, experiences and challenges with PrEP to understand what motivates or limits PrEP uptake and adherence specifically during pregnancy among this population of young women. Semi-structured interviews were conducted with 23 participants, recruited from the Prevention on PrEP (POPPi) study in the Good Health for Women Project clinic in Kampala, Uganda. POPPi's inclusion criteria comprised of HIV-uninfected women, aged 15-24, who exchange sex for money or commodities. Interviews focused on experience with PrEP and pregnancy. Data were analyzed utilizing a framework analysis approach. Key themes were comprised of participant barriers to and facilitators of PrEP uptake and adherence. Reasons for PrEP initiation included desire for autonomy and agency, mistrust of partners, and social support. Participants expressed challenges with initiating or sustaining their use of PrEP, including pregnancy, PrEP access and perceived or felt stigma. During pregnancy, participants' primary motivators for altering PrEP use were either understanding of PrEP safety for their baby or changes in perceptions of their HIV risk. Many of these factors were similar across participants who had experience with pregnancy and those who did not. This study highlights the importance of addressing barriers to and facilitators of PrEP uptake and persistence, especially during pregnancy where risk is elevated, with a multi-level approach. Community-oriented education, stigma reduction activities alongside access to PrEP, can serve as means for adherence. The development of robust PrEP support services and guidelines regarding PrEP use during pregnancy among high-risk women, and strategies for their implementation, are of utmost importance for the control of HIV in key populations and the elimination of mother-to-child transmission of HIV.